Challenges and opportunities of low-code platforms for software development - Mostbeck, Leonie (2022)
The current energy and climate crisis emphasize the energy-efficiency knowledge gap as a pressing problem. This is addressed in the report and the mobile application called EnMo, which was developed as part of this field lab. Topics regarding gamification, big data analytics, and low-code development were investigated. The findings provide the foundation for developing the app and its mission as a solution to the problem. EnMo incentivizes users to reduce their household energy consumption, by collecting user information and providing educational and gamified content. Thus, EnMo enables consumers to change their behavior and reduce their energy-efficiency knowledge gap. This exposition discusses the challenges and opportunity of low-code platforms for software development specifically. While speedy development, low maintenance and cost as well as low transparency and customization were filtered out as advantages of low-code, potential vendor lock-ins, black box issues and the fear of replacing software developers might present pitfalls of the technology.